Deep in the Fields of the Andromeda Halo: Discovery of the Pegasus VII Dwarf Galaxy in UNIONS - Simon E. T. Smith; Alan W. McConnachie; Stephen Gwyn; Christian R. Hayes; Massimiliano Gatto; Ken Chambers; Jean-Charles Cuillandre; Michael J. Hudson; Eugene Magnier; Nicolas Martin; Julio Navarro (The Astrophysical Journal)
We present the newly discovered dwarf galaxy Pegasus VII (Peg VII), a member of the M31 subgroup which has been uncovered in the ri photometric catalogs from the Ultraviolet Near-Infrared Optical Northern Survey and confirmed with follow-up imaging from both the Canada–France–Hawaii Telescope and the Gemini-North Telescope. This system has an absolute V -band magnitude of −5.7 ± 0.2 mag and a physical half-light radius of 177 ${}_{-34}^{+36}$ pc, which is characteristic of dynamically confirmed Milky Way satellite dwarf galaxies and about 5 times more extended than the most extended M31 globular clusters. Peg VII lies at a three-dimensional separation from M31 of 331 ${}_{-4}^{+15}$ kpc, and a significant elongation ( ϵ  ∼ 0.5) toward the projected direction of M31 could be indicative of a past tidal interaction, but additional investigation into the orbit, star formation history, and whether any gas remains in the galaxy is needed to better understand the evolution of Peg VII.